2021
DOI: 10.1177/23259671211033904
|View full text |Cite
|
Sign up to set email alerts
|

Return-to-Play Times and Player Performance After Medial Collateral Ligament Injury in Elite-Level European Soccer Players

Abstract: Background: Participation in elite-level soccer predisposes athletes to injuries of the medial collateral ligament (MCL), resulting in variable durations of time lost from sport. Purpose: To (1) determine the rate of return to play (RTP) and timing after MCL injuries, (2) investigate MCL reinjury incidence after RTP, and (3) evaluate the long-term effects of MCL injury on future performance. Study Design: Descriptive epidemiology study. Methods: Using publicly available records, we identified athletes who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Some Grade III MCL injuries are treated nonoperatively although operative management is recommended in patients with severe multi-ligamentous injury, chronic instability, distal avulsion with a Stener-type entrapment of the torn end in the medial compartment, and nonoperative management failure [ 15 ]. Nonoperative treatment has been shown to increase return to playtime and reinjury and decrease field time after return to play in elite-level athletes [ 16 ] These findings have caused most sports medicine orthopedic surgeons to select operative management of Grade III MCL tears in athletes [ 5 ]. Acevedo et al were one of the first to demonstrate the success of operative management in Grade III MCL tears with an appropriate post-operative protocol in Division I football athletes [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some Grade III MCL injuries are treated nonoperatively although operative management is recommended in patients with severe multi-ligamentous injury, chronic instability, distal avulsion with a Stener-type entrapment of the torn end in the medial compartment, and nonoperative management failure [ 15 ]. Nonoperative treatment has been shown to increase return to playtime and reinjury and decrease field time after return to play in elite-level athletes [ 16 ] These findings have caused most sports medicine orthopedic surgeons to select operative management of Grade III MCL tears in athletes [ 5 ]. Acevedo et al were one of the first to demonstrate the success of operative management in Grade III MCL tears with an appropriate post-operative protocol in Division I football athletes [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…24,30 Magnetic resonance imaging (MRI) studies have shown that concomitant medial injuries occur in as many of 67% of anterior cruciate ligament (ACL) injuries. 35 Nonoperative treatment of both low- and high-grade medial injuries before ACL reconstruction is commonplace, despite the presence of medial laxity at time zero, 5,21,26,35 and may result in good objective and patient-reported outcomes. Yet, a subset of patients have persistent medial laxity, 1,12,19 which may result in increased ACL graft strain and consequently increase the risk of ACL graft failure.…”
mentioning
confidence: 99%